2009
DOI: 10.1128/mcb.01357-08
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Compartmentalization of Base Excision Repair Proteins in Response to Nuclear and Mitochondrial Oxidative Stress

Abstract: DNAs harbored in both nuclei and mitochondria of eukaryotic cells are subject to continuous oxidative damage resulting from normal metabolic activities or environmental insults. Oxidative DNA damage is primarily reversed by the base excision repair (BER) pathway, initiated by N-glycosylase apurinic/apyrimidinic (AP) lyase proteins. To execute an appropriate repair response, BER components must be distributed to accommodate levels of genotoxic stress that may vary considerably between nuclei and mitochondria, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 96 publications
(145 reference statements)
7
60
0
Order By: Relevance
“…Indeed, the localization of many of the above described mitochondrial repair proteins could be dependent on the balance of damage between the nucleus and the mitochondria, similar to the translocation of CSB to the mitochondria after stress (Aamann et al, 2010; Stevnsner et al, 2008). In support, the cellular localization of the glycoslyase protein Ntg1, could be modulated using damage inducing agents (Griffiths et al, 2009). Stress induced re-localization of proteins including PARP and potentially FEN-1 could offer an explanation for the disparate mitochondrial localization reported for these proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the localization of many of the above described mitochondrial repair proteins could be dependent on the balance of damage between the nucleus and the mitochondria, similar to the translocation of CSB to the mitochondria after stress (Aamann et al, 2010; Stevnsner et al, 2008). In support, the cellular localization of the glycoslyase protein Ntg1, could be modulated using damage inducing agents (Griffiths et al, 2009). Stress induced re-localization of proteins including PARP and potentially FEN-1 could offer an explanation for the disparate mitochondrial localization reported for these proteins.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that this observation reflects the fact that mitochondria are a major source of ROS and that mitochondrial DNA is therefore particularly prone to oxidative damage. Interestingly, Griffiths et al [27] have also recently reported that in yeast, the intracellular location of the base excision repair protein Ntg1 is regulated by oxidative stress and that Ntg1 is able to localize to either nuclear or mitochondrial compartments in response to specific induction of oxidative stress in these two organelles. These findings show that regulation of base excision repair (BER) protein activity and location is complex and cells are able to rapidly adapt to meet specific oxidative challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Upon genotoxic insults a dynamic redistribution of DNA repair proteins to the site of damage is frequently observed; this phenomenon leads to the accumulation of DNA repair factors, often into spatially restricted foci. Relocalization events usually occur through cytoplasmic-mitochondrial, cytoplasmic-nucleoplasmic, and nucleolar-nucleoplasmic shuttling regulated by post-translational modifications (PTMs) and triggered by the damage itself (51).…”
Section: Dynamics Of Dna Repair Proteins During Genotoxic Damage: Nucmentioning
confidence: 99%